IMPORTANT REASONS FOR REFUSAL OF CONTRACEPTION AND THEIR FREQUENCY AND AWARENESS OF CONTRACEPTION AMONG LOW TO MIDDLE-INCOME POPULATION - BASHIR , S; QAZI , M; JUNEJO , S; NAWAZ , A; ARIJO , M; GHAZALA , . (Biological and Clinical Sciences Research Journal, 2024)
Contraception is a cornerstone of public health initiatives aimed at reducing unplanned pregnancies, improving maternal and child health outcomes, and empowering individuals to make informed reproductive choices. Objective: To identify the primary reasons for contraception refusal, assess the frequency of refusal, and evaluate awareness of contraceptive methods among individuals in low- to middle-income communities. Methods: This cross-sectional study was conducted at Shaikhzaid Women's Hospital Larkana from June 2024 to November 2024. Data were collected from 1200 participants. Participants were selected based on their willingness to participate and their ability to provide informed consent. Both men and women were included in the study to capture a broader understanding of contraceptive use, refusal, and awareness. Results: The study involved a total of 1,200 participants, with a majority of 800 females (66.7%) and 400 males (33.3%). The predominant age group was 25–35 years, accounting for 60% (n=720) of the sample, followed by 18–24 years at 25% (n=300) and 36–45 years at 15% (n=180). Regarding monthly household income, 70% (n=840) of participants reported incomes below the regional average, while 30% (n=360) had incomes above the regional average, highlighting the economic constraints faced by the majority of the population. Awareness of contraceptive methods was high for short-term options, with 75% (n=900) of participants knowing about condoms and 68% (n=816) aware of oral contraceptive pills. However, awareness of long-term methods like implants (40%, n=480) and intrauterine devices (35%, n=420) was relatively low, and only 20% (n=240) were familiar with emergency contraception. Conclusion: It is concluded that contraception refusal among low- to middle-income populations is influenced by a combination of cultural, economic, social, and informational barriers. Cultural and religious beliefs emerged as the most significant factors, followed by misconceptions about side effects and economic constraints.